Contact behavior between cracked surfaces of recycled aggregate concrete. (30th November 2017) - Sun, Chang; Lange, David A.; Xiao, Jianzhuang; Ding, Tao
Highlights: Contact behavior between fully cracked RAC surfaces is tested. Effect of curing time and aggregate type on contact behavior of concrete are analyzed. A reduction factor for modification of Walraven's model is suggested. Abstract: This paper develops a new test method to investigate the factors that influence contact behavior between fully cracked concrete surfaces. This test considers 36 specimens of recycled aggregate concrete (RAC) and conventional concrete. The material variables were the aggregate type (natural coarse aggregate (NCA) and recycled coarse aggregate (RCA)), surface roughness, and curing time before splitting (7 d and 28 d). Experimental results indicated that by increasing the gap between cracked surfaces from 0 mm to 4 mm, the maximum shear load was reduced, by 16.9–79% for different cases. Curing time and aggregate type were strong factors that affected the crack propagation and the contact behavior. Furthermore, for conventional concrete, increasing the curing time of concrete increased the maximum shear load by 0.47 times to 2.86 times; for RAC with higher quality RCA in this test, the shear load decreased by 21.8–65% with the increasing of curing time. The surface roughness has a positive effect on shear load, especially when the surface roughness increases greatly in this study. Walraven's model predicted stronger effect of interface roughness than shown by the results of these experiments, suggesting that these specimens had limited aggregate interlock. The results suggest that the Walraven model might be modified by an appropriate factor to better account for aggregate properties.